Administrative Burden in the Regional Disaster Management Agency (BPBD) of Semarang Province, Indonesia - Marta Solavide Naibaho; Lutfha, Mutiara (HM Publisher, 2024)
BPBD Semarang needs to focus on recruitment, training, performance assessment and managing employee needs. By having a team that is trained and ready, BPBD can respond to disasters quickly and efficiently. Data and information management requires collecting potential disaster data, risk mapping, and providing accurate information. Administrative burdens in this aspect include data collection, risk analysis, database management, and preparation of reports and related documents. Good financial management is the key to smooth operations. Administrative burdens involve budget planning, financial reporting, procurement of goods and services, and asset management, all of which must comply with regulations and transparency principles. BPBD Semarang needs to establish good coordination with government agencies, non-governmental organizations and the private sector. Administrative burdens include planning meetings, creating coordination protocols, and maintaining effective communication to ensure synergistic cooperation.